Treatment of embryonal tumors with multilayered rosettes with carboplatin/etoposide induction and highdose chemotherapy within the prospective P-HIT trial - Juhnke, Björn-Ole; Gessi, Marco; Gerber, Nicolas U.; Friedrich, Carsten; Mynarek, Martin; Bueren, André von; Haberler, Christine; Schüller, Ulrich; Kortmann, Rolf-Dieter; Timmermann, Beate; Bison, Brigitte; Warmuth-Metz, Monika; et al. (Neuro-Oncology, 2022)
Embryonal tumors with multilayered rosettes (ETMR) are highly aggressive tumors occurring in early childhood. Published clinical data refer to retrospective, heterogeneously treated cohorts. Here, we describe the outcome of patients treated according to the prospective P-HIT trial and subsequent HIT2000-interim-registry.Age-stratified treatment included carboplatin/etoposide induction, tandem high-dose chemotherapy (“CARBO/ETO + HDCT”), and response-stratified radiotherapy. Patients with centrally reviewed neuropathological and molecularly confirmed diagnosis of ETMR recruited within the P-HIT trial (2001-2011; n = 19), the HIT2000-interim-registry (2012-2014; n = 12), and earlier HIT trials (n = 4) were selected for analysis.Age-adjusted incidence rate was 1.35 per 1 million children (aged 1-4 years) in the years 2012-2014. Median age at diagnosis for 35 patients was 2.9 years. Metastases at diagnosis were detected in 9 patients. One patient died due to postoperative complications. For 30 patients with non-brainstem tumor location, 5-year progression-free survival (PFS) and overall survival (OS) were 35% and 47% after treatment with CARBO/ETO + HDCT (n = 17), compared to 0% and 8% with other treatments (n = 13, P[OS] = .011). All 4 patients with brainstem tumor died within 10 months after diagnosis. By multivariable analysis, supratentorial location: (HR [PFS]: 0.07 [95%CI: 0.01-0.38], P = .003), localized disease (M0): (HR [OS] M0, no residual tumor: 0.30 [95%CI: 0.009-1.09], P = .068; M0, residual tumor: 0.18 [95%CI: 0.04-0.76], P = .020), and CARBO/ETO + HDCT treatment (HR [OS]: 0.16 [95%CI: 0.05-054], P = .003) were identified as independent prognostic factors. Of 9 survivors, 6 were treated with radiotherapy (craniospinal 4; local 2).Our data indicate improved survival with intensified chemotherapy (CARBO/ETO + HDCT). However, despite intensive treatment, the outcome was poor. Thus, innovative therapies need to be evaluated urgently in an upfront setting.